Labor-intensive public works programs in sub-Saharan Africa: Experiences and implications for employment policies - Tekalign Gutu Sakketa; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2019)
Public works programs (PWPs) in sub-Saharan African countries have re-emerged as an important policy to stimulate employment generation in addition to their protective role such as consumption smoothening. The paper reviews evidence on the extent to which empirical research can substantiate the claim that labor-intensive PWPs in African countries have important economic benefits. We also refer to the experiences with PWPs in India and China for comparison. We aim to answer the following questions: Do PWPs stimulate job creation and raise earning potentials of beneficiaries? And, how do these programs augment employment generation. Based on our review complemented with secondary data analyses, we conclude that in addition to their role as an effective anti-poverty instrument, labor-intensive PWPs have important roles in mitigating poor labor market outcomes and thus enhance employment creation. Yet we also find that more systematic investigations on shortterm implementation outcomes of PWPs are necessary, and − due to externalities that are not captured by short-term assessments at the program level − long-run impacts on employment and development also need more research attention.
Keywords: H53; I38; J33; J38; 330; Employment; public works programs; social protection; Africa